Dislocation distribution in ruby single crystals under loading at high temperatures - Bosin, M.E.; Zvyagintseva, I.F.; Zvyagintsev, V.N.; Lavrentyev, F.F; Nikiforenko, V.N. (Functional Materials, 2004)
Evolution of dislocation structure in ruby single crystals under four-point bending at T = 1490°C has been studied using the etch pit method. The small-angle substructure boundaries have been observed, the dislocation types have been identified and their densi -ties have been measured. The screw and edge dislocation _density has been shown to be distributed symmetrically about the sample neutral axis [1100]] and about the [0001] one. The starting shear stress has been first measured and found to be 200 MPa in the prismatic slip system. This value is associated with the friction stress of the crystal lattice, that is, with the Peierls-Nabarro stress value in the (1100) prism plane along the [1120] direction. The starting stress value is to be known to treat thermomechanically high-perfection ruby single crystals and to solve the problem of long-term laser stability. Методом ямок травления исследовалась эволюция дислокационной структуры в монокристаллах рубина при 4-х точечном изгибе при температуре T = 1490°C. Выявлены субструктурные малоугловые границы, идентифицированы виды дислокаций и измерены их плотности. Показано, что плотность винтовых и краевых дислокаций распределяется симметрично относительно нейтральной оси образца [1100] и относительно оси [0001]. Впервые измерена величина сдвигового стартового напряжения, которая в системе призматического скольжения оказалась равной 200 МПа. Эта величина связывается с напряжением трения кристаллической решетки, то есть с величиной напряжения Пайерлса-Набарро в плоскости призмы (1100) в направлении [1120]. Отмечается, что величина стартового напряжения необходима для использования термомеханической обработки высокосовершенных монокристаллов рубина и решения проблемы долговременной работоспособности лазеров. Методом ямок травлення досліджєно єволюцію дислокаційної структури у монокристалах рубіну при чотирьохточковому вигині при температурі Т = 1490°С. Виявлено субструктурні малокутові границі, ідентифіковано види дислокацій та виміряно їх густини. Показано, що густина гвиртових та крайових дислокацій розподіляється симетрично відносно нейтральної осі зразка [1100] та відносно осі [0001]. Вперше виміряно величину стартової напруги зсуву, котра у системі призматичного ковзання виявилася рівною 200 МПа. Ця величина пов’язується з напругою тертя кристалічно_ гратки, тобто, з_ величиною напруження Пайєрлса-Набарро у площині призми (1100) у напрямі [1120]. Величина стартової напруги є необхідною для застосування термомеханічної обробки високодосконалих монокристалів рубіну та для вирішення проблеми довготривалої працездатності лазерів.